Droplet Microfluidics: Coding of Experimental Conditions in Microfluidic Droplet Assays Using Colored Beads and Machine Learning Supported Image Analysis (Small 4/2019). Issue 4 (24th January 2019) - Svensson, Carl‐Magnus; Shvydkiv, Oksana; Dietrich, Stefanie; Mahler, Lisa; Weber, Thomas; Choudhary, Mahipal; Tovar, Miguel; Figge, Marc Thilo; Roth, Martin
Abstract : In article number1802384, Miguel Tovar, Marc Thilo Figge, and co‐workers encode a population of microfluidic pico‐liter droplets with colored polystyrene beads for the simultaneous study of multiple experimental conditions. Droplets are imaged using brightfield microscopy and are successfully decoded and evaluated by machine learning supported image analysis. The novel encoding strategy is applied to antibiotic susceptibility testing of droplet‐encapsulated E. coli bacteria as a proof‐of‐principle.